Empagliflozin as treatment in glycogen storage disease type IB patients - María Arbelo Rodríguez; Elena Márquez Mesa; Cristina Lorenzo González; Marina Gutiérrez Vilar; Loredana Arhip; Mónica Ruiz Pons; José Pablo Suárez Llanos (Molecular Genetics and Metabolism Reports)
Background: Glycogen Storage Disease Ib (GSD Ib) is a disease that associates both neutropenia and neutrophil dysfunction, thereby causing recurrent infections and inflammatory bowel disease (IBD). As of now, the standard treatment of these complications has been the administration of granulocyte-stimulating factor (GCSF). However, recent studies have found that the use of empagliflozin, an antidiabetic drug, may have benefits by reducing the levels of 1,5 anhydroglucitol-6-phosphate (1,5-AG6P), a metabolite that accumulates in the cytosol of neutrophils and blocks the use of glucose. Results: We therefore report our experience with three patients, one of them being a liver and kidney transplant recipient, with promising results. Morbidity has been greatly reduced in all cases consisting in weight gain, better neutrophil count and management of respiratory, osteoarticular and gastrointestinal comorbidities. Overall, an improvement in quality of life has been observed. Conclusion: SGLT2 inhibitors, and specifically empagliflozin offer promising results in improving morbidity and quality of life in patients with GSD Ib. In the cases presented, including a patient with double liver-kidney transplant, a good profile of tolerance, safety and effectiveness has been observed. Synopsis: Empagliflozin offers promising results in improving morbidity and quality of life in patients with GSD Ib, including the first double organ transplant patient treated with this drug.